Clichés and pragmatemes - Mel’čuk, Igor (Neophilologica, 2020)
In order to properly classify the phraseme (that is, a constrained, or non-free, expression) No parking, a universal typology of lexical phrasemes is proposed. It is based on the following two parameters: • The nature of constraints — Lexemic phrasemes: the expression is constrained with respect to freely constructed meaning. — Semantic-lexemic phrasemes: the expression is constrained/non-constrained with respect to the meaning constrained by the conceptual representation. — Pragmatemes: the expression is constrained with respect to pragmatic conditions, that is, to the extralinguistic situation of its use (in a letter, on a street sign, on a package of perishable food). • The compositionality The expression can/cannot be represented as regular “sum” of its components. As a result, we have, firstly, the following major classes of lexical phrasemes: 1) Non-compositional lexemic phrasemes: idioms (˹cold feet˺, ˹shoot the breeze˺) 2) Compositional lexemic phrasemes: collocations (rain heavily, pay a visit) 3) Non-compositional semantic-lexemic phrasemes: nominemes (Big Dipper, New South Wales) 4) Compositional semantic-lexemic phrasemes: clichés (See you tomorrow! | Absence makes the heart grow fonder.) For clichés, the least-studied class of phrasemes, a more detailed classification is proposed (as a function of the type of their denotation). Secondly, each phraseme (except a nomineme) and each lexemes can be pragmatically constrained, i.e. a pragmateme: ˹Fall out!˺ (idiom; a military command) | Take aim! (collocation; a military command) | Emphasis mine/added (cliché; in a printed text) | Rest! (lexeme; a military command).